2005
DOI: 10.1080/00288233.2005.9513686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variation in shade level, shade duration and light quality on perennial pastures

Abstract: Two experiments examining the effect of artificial shade on pasture net herbage accumulation (NHA), botanical composition and soil characteristics were conducted between 1994 and 1999 at Whatawhata Research Centre. Both experiments included a range of shade levels (0-94%) and shade durations (3-12 months per year). Experiment 1 also included a light quality treatment, incorporating a range in the red:far red ratio (0.49-1.00). All three shading factors decreased annual NHA, with the most influential being the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 20 publications
3
24
1
1
Order By: Relevance
“…These trends are similar to the overall patterns found across all species in woodlands and that might reflect a general response of grassland species to light availability (Dodd et al . ). Although alien herbaceous species can in some cases reduce native tree species richness by limiting regeneration (Rogers ; Flory & Clay ; Thomsen et al .…”
Section: Discussionmentioning
confidence: 97%
“…These trends are similar to the overall patterns found across all species in woodlands and that might reflect a general response of grassland species to light availability (Dodd et al . ). Although alien herbaceous species can in some cases reduce native tree species richness by limiting regeneration (Rogers ; Flory & Clay ; Thomsen et al .…”
Section: Discussionmentioning
confidence: 97%
“…Pruning caused an increase in PPF (Table 2), maintained the R:FR and decreased soil temperature (Table 4). Light was limiting for pasture growth in the heavy shade throughout the growing season (Dodd et al 2005;Peri et al 2007), and the sward was observed to be less densely tillered (Table 6) due to the morphological responses of the pasture species to the low R:FR in the heavy shade. Additionally, sheep preferred grazing in light shade as opposed to heavy shade ( Table 9), suggesting that utilisation and grazing management of the pasture in heavy shade would be more difficult than in light shade (Peri et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Understorey pasture production normally depends on the degree of competition between trees and pasture for light, moisture, and nutrients (Dodd et al 2005;Eastham and Rose 1988). Studies on Pinus radiata in New Zealand indicated that understorey herbage production decreases as crown density increases (Hawke and Knowles 1997;Pollock et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Light intensity, soil moisture and nutrients are three major growth resources that determine productivity of silvopastoral and savanna ecosystems (Belsky 1994;Dodd et al 2005;Burner and MacKown 2006;Koukoura et al 2009). Trees in the systems create a horizontal structure above grasses (Sarmiento 1984;Tournebize and Sinoquet 1994) and modify availability of the growth resources (Vetaas 1992;Polley et al 1997;Benavides et al 2009) and thereby influence growths and yields of the grasses by facilitative or competitive mechanisms (Belsky 1994;Callaway and Walker 1997).…”
Section: Introductionmentioning
confidence: 99%